(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This is it in the article Nizamuddin Shami and " Zafarnoma " is the name of Sharafuddin Ali Yazdi with famous historical His works are from the 14th-15th centuries Temur and The Timurids rule period Central Asia , Gold Horde Khanate , Azerbaijan , Iran , Afghanistan , Iraq , Syria , Egypt , Turkey and another countries to history about events own into received about briefly information is given In the article main attention to both of the XIV century in the work second half and of the XV century At the beginning of In Mowarannahr happen was important historical processes to the analysis directed .